Pengayaan Nutrisi (fortifikasi) pada Olahan Singkong Berbasis Partisipatoris - Susilowati, Dwi; Mardiyani, Siti Asmaniyah (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2019)
Southern Malang region is the center of cassava producers in Malang Raya area. In Tempursari Village, Donomulyo District, Malang Regency, processing of cassava has not been done optimally. There has been limited effort to enrich the processed cassava with additional high nutrition. Cassava peel waste also has not been utilized optimally by the residents. Therefore, counseling and advocacy activities of nutrition enrichment technology on cassava processing is essential to be applied. Service activities were done through diffusion activities related to the application of cassava processing technology to Islamic Women Organization based on Nahdhatul Ulama (Muslimat-NU) board in Tempursari Village, Donomulyo District, Malang in a participatory way. The technology applied was a simple nutrient fortification technology, with green bean-crushed cassava steam, cassava brownies, protein-rice cassava rice, protein-rich cassava flour, natural healthy cassava peel sauce. The results of this activity were: a. There was an increasing pattern of public understanding of the importance of cassava enrichment nutrition among the participants. It encouraged them to do various innovations in creating high economic value of cassava processed food. b. There was an increasing pattern of skill society in adopting cassava processing fortification technology. It showed that feasibility of cassava as the resource of nutritious staple food increased. Therefore the community will become more productive and innovative, and the technology disseminated in this activity could be further developed and popularized.